2014
DOI: 10.1186/1472-6882-14-127
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture improves recovery after hemorrhagic brain injury by inducing the expression of angiopoietin-1 and -2 in rats

Abstract: BackgroundAngiopoietin (Ang) is one of the major effectors of angiogenesis, playing a critical role in neurovascular remodeling after stroke. Acupuncture has been widely used for treating stroke in China for a long time. Recently, we have demonstrated that electroacupuncture (EA) can accelerate intracerebral hemorrhage (ICH)-induced angiogenesis in rats. In the present study, we investigated the effect of EA on the expression of Ang-1 and Ang-2 in the brain after ICH.MethodsICH was induced by stereotactic inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Therefore, attenuating of neuroinflammation effectively protects brain, which is considered as an important therapeutic strategy for improving neurological function after ischemic stroke [19][20]. Studies have demonstrated that EA at the acupoints attenuate inflammation for limiting neurological deficits in brain injury following ischemic stroke [21][22][23]. Our previous studies have found that EA at the LI 11 and ST 36 acupoints improved the ischemia-associated scores of neurological deficits via inhibition of the toll-like receptor (TLR) 4/NF-κB signaling pathway following focal cerebral ischemia [24].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, attenuating of neuroinflammation effectively protects brain, which is considered as an important therapeutic strategy for improving neurological function after ischemic stroke [19][20]. Studies have demonstrated that EA at the acupoints attenuate inflammation for limiting neurological deficits in brain injury following ischemic stroke [21][22][23]. Our previous studies have found that EA at the LI 11 and ST 36 acupoints improved the ischemia-associated scores of neurological deficits via inhibition of the toll-like receptor (TLR) 4/NF-κB signaling pathway following focal cerebral ischemia [24].…”
Section: Introductionmentioning
confidence: 99%
“…EA at the Zusanli acupoint has been shown to accelerate intracerebral hemorrhage (ICH)-induced angiogenesis in rats (Luo et al, 2013). After EA to the bilateral Zusanli (ST36) acupoint in adult rats, the expression of Ang-1 (from 3 days to 14 days) and Ang-2 (at 3 days) was upregulated after hemorrhagic stroke at both the protein and mRNA levels (P<0.05), thus exerting neuroprotective effects (Zhou et al, 2014). Furthermore, EA has also exhibited an anti-inflammatory effect after stroke in rats .…”
Section: Ea Inhibits Neuronal Apoptosis and Induces Tolerance Againstmentioning
confidence: 99%
“…It is currently believed that angiogenesis promotes neurogenesis since it supports the recovering neural networks (Ohab et al, 2006). The angiopoietin (Ang) family, including Ang-1 and Ang-2, is one of the major effectors of angiogenesis (Zhou et al, 2014). Ang-1 and Ang-2 have been shown to regulate ischemia-induced angiogenesis in rat brains .…”
Section: Ea Inhibits Neuronal Apoptosis and Induces Tolerance Againstmentioning
confidence: 99%
“…In routine clinic, the treatment of acute ICH mainly adopts the western conventional medicine (WCM), such as preventing further bleeding, controlling brain edema, decreasing intracranial pressure, maintaining life function, and preventing complications (Dimitre et al, 2010). Obviously, the actual efficacy of the WCM alone does not meet expectations (Andaluz and Zuccarello, 2009;Zhou et al, 2014). Therefore, new treatment drugs need to be developed under the guidance of evidence-based medicine.…”
Section: Introductionmentioning
confidence: 99%